Blockchain Based Authentication and Authorization Framework for Remote Collaboration Systems - Widick, Logan; Ranasinghe, Ishan; Dantu, Ram; Jonnada, Srikanth (2019 IEEE 20th International Symposium on "A World of Wireless, Mobile and Multimedia Networks" (WoWMoM), 2019)
Due to the advantages of blockchain technologies, including decentralization, immutability, transparency and security, people try to replace existing problematic architectures /frameworks with blockchain based ones. In this paper we propose a novel authentication and authorization framework based on blockchain technologies to control access to the resources of an IoT device. In this paper, we focus on devices such as the Cyber Handyman used in remote collaboration applications to develop our framework. We tested our smart contracts on the Ropsten test network. Our results showed that it can handle 25 service requests simultaneously.
Keywords: Access Control; authorization; blockchain; Digital Certificate; IoT; remote collaboration; Security

Verifying OAuth Implementations Through Encrypted Network Analysis - Talkington, Josh; Dantu, Ram; Morozov, Kirill (Proceedings of the 24th ACM Symposium on Access Control Models and Technologies, 2019)
Verifying protocol implementations via application analysis can be cumbersome. Rapid development cycles of both the protocol and applications that use it can hinder up-to-date analysis. A better approach is to use formal models to characterize the applications platform and then verify the protocol through analysis of the network traffic tied to the models. To test this method, the popular protocol OAuth is considered. Currently, formal models of OAuth do not take into consideration the mobile environment, and implementation verification is largely based on code analysis. Our preliminary results are two fold; we sketch an extension to a formal model that incorporates the specifics of the Android platform and classify OAuth device types using machine learning on encrypted VPN traffic.
Keywords: Android; authorization; formal models; network analysis; oauth